The independent prognostic impact of the GATA2 pioneering factor is restricted to ERG-negative prostate cancer - Franziska Büscheck; Maciej Zub; Asmus Heumann; Claudia Hube-Magg; Ronald Simon; Dagmar S Lang; Doris Höflmayer; Emily Neubauer; Frank Jacobsen; Andrea Hinsch; Andreas M Luebke; Maria Christina Tsourlakis; et al. (Tumor Biology, 2019)
GATA2 is a pioneering transcription factor governing androgen receptor expression and signaling in prostate cells. To understand the prognostic potential of GATA2 assessment in prostate cancer, we analyzed nuclear GATA2 expression on an annotated tissue microarray with 12,427 prostate cancer samples. Normal prostate glands were negative to weakly positive. GATA2 staining was found in almost all prostate cancers (95%). Strong GATA2 staining was linked to advanced tumor stage, high classical and quantitative Gleason grade (p < 0.0001 each), positive nodal stage (p = 0.0116), and early biochemical recurrence (p < 0.0001). GATA2 was linked to ERG -fusion-type cancers, with strong GATA2 staining in 29% of ERG-negative and 53% of ERG-positive cancers (p < 0.0001). Separate calculations in 3854 cancers with and 4768 cancers without TMPRSS2:ERG fusion revealed that these associations with tumor phenotype and patient outcome were largely driven by the subset of ERG-negative tumors. GATA2 expression was further linked to androgen receptor expression: Only 8% of androgen receptor-negative, but 56% of strongly androgen receptor expressing cancers had strong GATA2 expression (p < 0.0001). In conclusion, the results of our study demonstrate that increasing GATA2 levels are linked to prostate cancer progression and aggressiveness. The prognostic value of GATA2 is remarkable in ERG-negative cancers. However, the upregulation of GATA2 in ERG-positive cancers makes it unsuitable as a prognostic marker in this patient subset.